“There Is something Rotten in Denmark”: Investigating the Deepfake persona perceptions and their Implications for human-centered AI - Kaate, Ilkka (Elsevier, 2025)
Although they often have a negative connotation due to their social risks, deepfakes have the potential to improve HCI, human-centered AI, and user experience (UX). To investigate the impact of deepfakes on persona UX, we conducted an experimental study with 46 users who used a deepfake persona and a human persona to carry out a design task. We collected think-aloud, observant notes, and survey data. The results of our mixed-method analysis indicate that if users observe glitches in the deepfake personas, these glitches have a detrimental effect on the persona UX and task performance; however, not all users identify glitches. Our quantitative analysis of survey data shows that there are differences in how (a) users perceive deepfakes, (b) users detect deepfake glitches, (c) deepfake glitches affect information comprehension, and (d) deepfake glitches affect task completion. Glitches have the most significant impact on authenticity, persona perception, and task perception variables but less impact on behavioral variables. The results imply that organizations implementing deepfake personas need to address perceptual challenges before the full potential of deepfake technology can be realized for persona creation.